Integrating Islamic Law and Customary Law: Codification and Religious Identity in the Malay Buyan Community of Kapuas Hulu - Zaimuariffudin Shukri Nordin; Ismail Ruslan; Yusriadi Yusriadi; Nur Hamzah; Didi Darmadi (Journal of Islamic Law)
This article analyzes the integration of Islamic law and customary law in shaping the religious identity of the Malay Buyan community in Kapuas Hulu, West Kalimantan, Indonesia. While Islamic law plays a central role in regulating social and religious life, local customary law remains deeply embedded in the community’s legal consciousness and socio-cultural framework. Previous studies have often treated these two legal systems as separate or even contradictory. However, this study challenges such a dichotomous perspective by demonstrating that Islamic law and customary law engage in an ongoing process of negotiation, resulting in an adaptive and contextually dynamic legal framework. Using a socio-legal approach, this research collects data through in-depth interviews with ten key informants, participant observation, and document analysis. The findings reveal that Islamic law does not replace customary law but is instead integrated into the local legal system, influencing various aspects of social order, family structures, and the sustainable management of natural resources. This integration is evident in the use of Islamic legal terminology, the substance of legal norms, the mechanisms for customary fines, and the role of Islamic religious leaders in the codification of customary law. These findings challenge the prevailing bipolar view that positions Islamic law and customary law as inherently opposing systems. Instead, this study highlights a dynamic and integrative interaction between the two legal traditions, ensuring both social harmony and legal continuity. Ultimately, the article argues that the coexistence of Islamic and customary law is not a source of conflict but a mutually reinforcing and evolving process that contributes to strengthening both religious and cultural identity in a predominantly Muslim society.